2021
DOI: 10.1111/ejn.15094
|View full text |Cite
|
Sign up to set email alerts
|

Role of angiotensin receptors in the medial amygdaloid nucleus in autonomic, baroreflex and cardiovascular changes evoked by chronic stress in rats

Abstract: This study investigated the role of AT1, AT2 and Mas angiotensinergic receptors within the MeA in autonomic, cardiovascular and baroreflex changes evoked by a 10‐day (1  hr daily) repeated restraint stress (RRS) protocol. Analysis of cardiovascular function after the end of the RRS protocol indicated increased values of arterial pressure, without heart rate changes. Arterial pressure increase was not affected by acute MeA treatment after the RRS with either the selective AT1 receptor antagonist losartan, the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 87 publications
(142 reference statements)
0
4
0
Order By: Relevance
“…4 Our results show that CRS induced an increase in blood pressure, as previously shown. 51–53 This rise in blood pressure during chronic stress could be attributed, among other mechanisms, to (1) impairments in baroreflex and sympathetic responses 53 ; (2) elevated NE levels 12 ; (3) vascular oxidative stress 54 ; and (4) vascular dysfunction. 52 Notably, we found that the treatment with NaHS restored blood pressure to physiological levels in animals with chronic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…4 Our results show that CRS induced an increase in blood pressure, as previously shown. 51–53 This rise in blood pressure during chronic stress could be attributed, among other mechanisms, to (1) impairments in baroreflex and sympathetic responses 53 ; (2) elevated NE levels 12 ; (3) vascular oxidative stress 54 ; and (4) vascular dysfunction. 52 Notably, we found that the treatment with NaHS restored blood pressure to physiological levels in animals with chronic stress.…”
Section: Discussionmentioning
confidence: 99%
“…4 Our results show that CRS induced an increase in blood pressure, as previously shown. [51][52][53] This rise in blood pressure during chronic stress could be attributed, among other mechanisms, to (1) impairments in baroreflex and sympathetic responses 53 ;…”
Section: Nahs Administration Reestablishes Hemodynamic Variables and ...mentioning
confidence: 99%
“…One day before the trial, rats were anesthetized with tribromoethanol (250 mg/kg, i.p. ), and a catheter (Clay Adams, Parsippany, NJ, USA) filled with a solution of heparin (50UI/ml, Hepamax-S, Blausiegel, Cotia, SP, Brazil) diluted in saline (0.9% NaCl) was inserted into the abdominal aorta through the femoral artery for cardiovascular recording, according to procedures previously described by our group 13 , 57 , 59 , 60 . After the surgery, the non-steroidal anti-inflammatory flunixin meglumine (0.5 mg/ml/kg, s.c.) was administered for post-operation analgesia.…”
Section: Methodsmentioning
confidence: 99%
“…All rats were allowed at least 60 min to adapt to the sound and illumination conditions of the room (25 °C and acoustically isolated) before starting the experiment. Afterwards, animals randomly received bilateral microinjections into the MeA of the selective AT 1 receptor antagonist losartan (1 nmol/100 nL, n = 9), the selective MAS receptor antagonist A-779 (0.1 nmol/100 nL, n = 10), the selective AT 2 receptor antagonist PD12319 (0.5 nmol/100 nL, n = 8) or vehicle (NaCl 0.9%, 100 nL, n = 21) [ 42 , 51 , 52 , 53 ]. Ten minutes after the drug microinjection into the MeA, the animals underwent the 60 min session of restraint stress.…”
Section: Methodsmentioning
confidence: 99%